Vivid-memory formation through experiential value in the context of the international industrial exhibition. Issue 3 (24th March 2017) - Ahn, Young-joo; Hyun, Sunghyup Sean; Kim, Insin
ABSTRACT: This study empirically tests the relationships between experiential value, vividness, storytelling intentions, and patronage intentions in the industrial exhibitions, and examines the moderating effect of mementos. A total of 211 respondents were recruited from visitors to the international game exhibition. According to the results, (1) three dimensions of experiential value (service excellence, playfulness, and aesthetics) had positive effects on vividness, (2) vividness positively influenced storytelling and patronage intentions, (3) storytelling intentions increased patronage intentions, and (4) mementos had a significant moderating effect on the relationship between vividness and storytelling intentions but not on the relationship between vividness and patronage intentions.